Simulation of Turbulent Convection at High Rayleigh Numbers. (9th January 2018) - Dmitriev, Sergey; Kozelkov, Andrey; Kurkin, Andrey; Tarasova, Nataliya; Efremov, Valentin; Kurulin, Vadim; Shamin, Roman; Legchanov, Maksim
Abstract : The paper considers the possibility of using different approaches to modeling turbulence under conditions of highly developed convection at high Rayleigh numbers. A number of industrially oriented problems with experimental data have been chosen for the study. It is shown that, at Rayleigh numbers from 10 9 to 10 17, the application of the eddy-resolving LES model makes it possible to substantially increase the accuracy of modeling natural convection in comparison with the linear vortex viscosity model SST. This advantage is most pronounced for cases of a vertical temperature difference with the formation of a large zone of convection of strong intensity. The use of the Reynolds stress model EARSM is shown for cases of natural convective flow in domains with dihedral angles in the simulated region and the predominance of secondary currents. When simulating a less intense convective flow, when the temperature difference is reached at one boundary, the differences in the approaches used to model turbulence are less significant. It is shown that, with increasing values of Rayleigh numbers, errors in the determination of thermohydraulic characteristics increase and, for more accurate determination of them, it is expedient to use eddy-resolving approaches to the modeling of turbulence.